The effectiveness of family enrichment model for work on marital satisfaction, career and work-family conflict of married female managers - Makipour , Sara; Shafiabadi, Abdollah; Falsafinejad, Mohammadreza; Khodabakhshi-koolaee , Anahita (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was the effectiveness of family enrichment model for work on marital satisfaction, job satisfaction and work-family conflict of married female managers. Methods: The present study was a semi-experimental study with an experimental and control group and a pre-test-post-test design with a six-month follow-up. The statistical population included all 150 married female managers working in the headquarters department of Persian Bank in Tehran in 2021, who along with their spouses were willing to participate in training sessions. The number of sample members was 30 couples who were replaced by random sampling in two experimental and control groups (15 couples in the experimental group and 15 couples in the control group). The experimental group was subjected to the intervention of the family enrichment model for the work of Makipour et al (2021) for 9 sessions of 90 minutes. Both groups were evaluated in the three stages of pre-test, post-test and follow-up by Enrich marital satisfaction questionnaires (1989), Minnesota job satisfaction scale (1943) and Rostgarkhald’s work-family conflict scalhe (2002). Data were analyzed using repeated measures mixed analysis of variance. Results: The results indicate the effect of family enrichment intervention for work on the score of marital satisfaction (P < 0.05, F = 6.07) and job satisfaction (P < 0.05, F = 60.32) in female managers, as well as the score Work-family conflict (P < 0.05, F = 8.17), marital satisfaction (P < 0.05, F = 18.53) and job satisfaction (P < 0.05, F = 69.72) in Spouses and lack of effect of family enrichment intervention for work on work-family conflict score (P < 0.05, F = 0.95) in female managers and the stability of these results was in the follow-up phase. Conclusion: Considering the results obtained from the research, organizational managers can benefit from the educational model of family enrichment for work as an effective intervention method to improve the marital and job satisfaction of married female managers and couples and reduce the work-family conflict of both working couples.